Coefficient Test of Antimicrobial Phenol Combination of Eichhornia crassipes and Pistia stratiotes Extract In Vitro as Alternative Disinfection Candidates - Budiarti, Lia Yulia; Kaidah, Siti; Azhari, Nazla Puteri; Putri, Putri (Berkala Kedokteran, 2023)
Eichhornia crassipes and Pistia stratiotes are weeds that often pollute water areas. These two contain various active compounds that act as antimicrobials, which have the potential as disinfection agents to prevent the transmission of pathogenic bacteria and fungi. An antimicrobial substance is said to be effective as a good disinfectant if it has a phenol coefficient value equal to or more than the 5% phenol comparison substance. The aim of this research was to test the effectiveness of a combination of Eichhornia crassipes and Pistia stratiotes extracts as a disinfection candidate through the phenol coefficient test. This in vitro experimental study was carried out using a dilution technique. The combination treatment of Eichhornia crassipes and Pistia stratiotes extracts and 5% phenol was tested against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi and also Candida albicans yeast. Observations on the test media suspension tubes that were clear or did not show the growth of the test microbes for a period of 5, 10, and 15 minutes. The phenol coefficient value of the combination treatment of Eichhornia crassipes and Pistia stratiotes extracts was ≥1 with 5% phenol as comparison. Higher coefficient values were obtained for Staphylococcus aureus, equivalent values of 5% phenol were found for E.coli, P.aeruginosa, and C.albicans; whereas in S.typhi the value is <1. The combination treatment of E.crassipes and P.stratiotes extracts resulted in a phenol coefficient value equivalent to that of 5% phenol comparator, for several tested bacteria and yeasts. So it has effectiveness as a preparation for disinfection. The combination of Eichhornia crassipes and Pistia stratiotes extracts has antimicrobial effectiveness and can be developed as an alternative disinfection candidate.